Asthma in British Columbia: Are we finally breathing easier? A population-based study of the burden of disease over 14 years. (16th March 2017) - Bardal, Stan; Smith, Anne; Luo, Hao (Allan); Zhang, Tingting; Groeneweg, Gabriella; Jimenez Mendez, Ricardo; Goldman, Ran; Carleton, Bruce C.
ABSTRACT: Objective : Asthma presents a significant global burden, but whether the incidence and prevalence of asthma is rising is still debated. The objective of this study was to determine the prevalence and incidence of asthma in British Columbia (BC), Canada, and characterize associated health services utilization. Methods : We extracted data from provincial administrative hospitalization, medical services, and prescription drug databases for patients aged 5 to 55 years, during 1996 to 2009 having ≥270 MSP registration days and meeting asthma definition of: ≥1 hospital admissions with asthma as the principal diagnosis, or ≥2 physician visits for asthma as the principal diagnosis, or ≥3 asthma drug dispensings. Regression models were used to test change in asthma incidence and prevalence, and use of various health care services, such as physician and emergency department (ED) visits, and hospitalizations. Results : 379, 950 patients met the study criteria. The prevalence (2.6%) and incidence (0.7%) of asthma was relatively stable over the study period. There was a decline in proportion of patients visiting family practitioners (FP) (OR 0.92; 95% CI 0.90–0.94), specialists (OR 0.60; 95% CI 0.58–0.62), using ED services (OR 0.31; 95% CI 0.30–0.32) and hospitalizations (OR 0.34; 95% CI 0.31–0.37). Regional differences were noted, with lower rates of FP and specialist visits and higher rates of ED visits for asthma in rural versus urban areas. Conclusions : In BC, the incidence and prevalence of asthma has remained stable over 14 years. Although health service utilization declined, there is variation between rural and urban regions.